Strategies for the Implementation of Inclusive Education in Humbang Hasundutan Regency - Elsina Sihombing; Jecson Pangihutan Sihombing; Edward Coco Priyono Pardede; Surta Helena Ambarita; Rani Manurung; Ani Bertha Simamora (Jurnal Sosial Sains dan Komunikasi, 2026)
Inclusive education is an educational approach that provides equal opportunities for all students, including children with special needs, to obtain proper educational services without discrimination. This study aims to describe the implementation of inclusive education in schools, covering the learning process, the role of teachers, facilities and infrastructure, as well as the supporting and inhibiting factors in its implementation. The research method used is a qualitative approach with a descriptive research design. Data collection techniques were conducted through observation, interviews, and documentation. The results of the study indicate that the implementation of inclusive education in schools has been carried out fairly well through curriculum adjustments, the use of flexible learning methods, and collaboration among teachers, parents, and the school. Teachers play an important role in creating a friendly learning environment that supports the diversity of students. However, the implementation of inclusive education still faces several obstacles, such as limited teacher competence in handling students with special needs, inadequate supporting facilities, and the lack of special assistant teachers. Therefore, continuous training for teachers, the provision of adequate facilities, and supportive school policies are needed so that inclusive education can be implemented optimally. This study is expected to serve as a reference for strategies in developing inclusive education in schools.